Empowering Student Entrepeneurship: A 21st Century Learning Approach using TPACK Integrated PjBL Model - Iskandar, Iskandar (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
The 21st century presents numerous challenges for students, particularly in developing entrepreneurial skills to thrive in a dynamic job market. This study investigates the efficacy of the TPACK integrated PjBL (Technological Pedagogical Content Knowledge integrated Project-based Learning) model in fostering students' entrepreneurial interests within the context of 21st century learning in Islamic Religious Education. A mixed methods research design was employed, involving data collection, analysis, and integration of quantitative and qualitative methods. The study encompassed 90 third-semester students enrolled in the Islamic Religious Education Study Program at UIN Sulthan Thaha Saifuddin Jambi, utilizing a total sampling technique. Statistical tests were conducted, including preliminary tests such as the Kolmogorov-Smirnov normality test on pretest and posttest data. The findings reveal a significant increase in students' interest in entrepreneurship following the implementation of TPACK-integrated and PjBL-based learning. It is evident that employing the TPACK integrated PjBL model positively influences students' entrepreneurial interest. These results have profound implications for educators and policymakers, highlighting the importance of integrating the TPACK integrated PjBL model within Islamic Religious Education to enhance entrepreneurial skills and better equip students for the competitive job market. Additionally, this study emphasizes the potential for further research on technology-enhanced pedagogical approaches across various educational contexts to foster the development of 21st century skills. The implications of this research provide educators and stakeholders with valuable insights into the utilization of the TPACK integrated PjBL model as a means to empower students' entrepreneurial interests.